Urban environmental determinants of respiratory health: The role of air pollution, housing conditions, and green open space - Tuti Yelvianti; Muhammad Fachri; Nurmalia Lusida (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Rapid urbanization has increased exposure to multiple environmental stressors including air pollution, inadequate housing, and limited access to green open spaces, all of which adversely affect respiratory health. Understanding the interplay of these factors is essential for developing evidence-based urban health policies. Purpose: To synthesize evidence on the determinants of urban environments — specifically air pollution, housing conditions, and green open spaces — and their effects on respiratory health outcomes. Method: This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Literature searches were conducted using keywords